A Dedicated Orthopaedic Trauma Room Improves Efficiency While Remaining Financially Net Positive. Issue 1 (January 2023) - Lex, Johnathan R.; Abbas, Aazad; Oitment, Colby; Wolfstadt, Jesse; Wong, Paul; Abouali, Jihad; Yee, Albert; Kreder, Hans J.; Larouche, Jeremie; Toor, Jay
Abstract : Objectives: To determine the impact of dedicated orthopaedic trauma room (DOTR) implementation on operating room efficiency and finances. Design: Retrospective cost-analysis. Setting: Single midsized academic-affiliated community hospital in Toronto, Canada. Participants: All patients that underwent the most frequently performed orthopaedic trauma procedures (hip hemiarthroplasty, open reduction internal fixation of the ankle, femur, elbow and distal radius), over a 4-year period from 2016 to 2019 were included. Intervention: Patient data acquired for 2 years before the implementation of a DOTR was compared with data acquired for a 2-year period after its implementation, adjusting for the number of cases performed. Main Outcome Measurements: The primary outcome was surgical duration. The secondary outcome was financial impact, including after-hours costs incurred and opportunity cost of displaced elective surgeries. Results: One thousand nine hundred sixty orthopaedic cases were examined pre- and post-DOTR. All procedures had reduced total operative time post-DOTR (mean improvement of 33.4%). The number of daytime operating hours increased 21%, whereas after-hours decreased by 37.8%. Overtime staffing costs were reduced by 24, 976 alongside increase in opportunity costs of 22, 500. This resulted in a net profit of 2476. Conclusions: Our results support the premise that DOTRs improve operating room efficiency and can be cost efficient. Our study also specifically addresses the hesitation regarding potential loss of profit from elective surgeries. Widespread implementation can improve patient care while still remaining financially favorable. Level of Evidence: Economic Level IV. See Instructions for Authors for a complete description of levels of evidence.